KAJIAN PERSEPSI DAN MOTIVASI PENGUNJUNG UNTUK PENGEMBANGAN WISATA ALAM DI PENANGKARAN RUSA TAHURA WAN ABDUL RACHMAN - Tiara Avissa Agung; Susni Herwanti (Jurnal Hutan Tropis, 2020)
Tourism is a promising option for developing countries in order to create a prosperous society. Indonesia with its natural wealth and hospitality has the potential to be one of the world's destination countries. One of the potential natural attractions that can be developed for tourism in Lampung Province is the Deer Captive of the Great Forest Park (Tahura) Wan Abdul Rachman. The aims of this study were to determine the perception and motivation of visitors to visit the Deer Captive of Tahura Wan Abdul Rachman. The information is important to provide input for further planning and management of the Deer Captive of Tahura Wan Abdul Rachman. The research was carried out in the Deer Captive of Tahura Wan Abdul Rachman. The study was conducted by interviewing visitors and sampling was done using incidental sampling techniques. The results showed that visitors' perceptions of the uniqueness of Timor Deer were very good, while for visitors' perceptions of accessibility it was stated to be quite good, perceptions of facilities were also stated to be good, and the perception of the addition of tour guides was very good to be included as ancillary services.  There are two factors that motivate visitors, namely drivers and pullers. The driving factor for visitors is to increase knowledge about Cervus timorensis and visitors' attracting factors, namely the attraction of Cervus timorensis.